A study of the archival system: Enhancing archive management - Bernadetha, Maria; Sauw, Heni Matelda; Engel, Stela Sahetapy; Maria, Maria; Kelen, Maria Sisilia Lou (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study investigates the archival management system focusing on improving its effectiveness and efficiency. The primary objectives are to evaluate the current archival practices, identify challenges and gaps, propose improvements, and enhance the overall archival management system. The research employs a qualitative methodology, incorporating interviews, observations, and document analysis to gather comprehensive data on the existing archival practices and issues. The analysis reveals several critical problems in the archival management system including inadequate human resources, insufficient storage facilities, lack of technological integration, poor maintenance practices, and security concerns. These issues contribute to inefficiencies in managing dynamic and static archives, affecting the accessibility and preservation of important records. Based on the findings, the study proposes several recommendations to address these challenges. These include the adoption of modern technology for digital archiving, the improvement of storage facilities to accommodate the growing volume of archives, enhanced maintenance practices to prevent damage, and the implementation of robust security measures to protect valuable records. The study concludes that by addressing these issues and implementing the proposed improvements, can significantly enhance the efficiency and effectiveness of its archival management system. This will lead to better preservation, accessibility, and security of archival records, ultimately supporting the institution's administrative functions and operational goals.